From Ideology to Economics: Understanding the Conflict between two Countries - Jamil, Ms. Shafia; Atta, Ms. Misbah; Sajjad, Aaliaba (Journal of Quranic and Social Studies, 2023)
Religious and ideological disparities have contributed to tensions between the two nations. The division of British India in 1947 along religious lines created a deep-seated divide, leading to ongoing conflicts. A key factor is the territorial dispute over Kashmir. Both countries claim Kashmir, resulting in multiple wars and persistent tensions. Political, military, and economic interests, as well as national pride, drive this dispute. India and Pakistan both seek regional dominance in South Asia. Kashmir’s strategic location near China adds complexity. Control over Kashmir allows Pakistan a land link with China, while India sees it as crucial for its territorial integrity. The legacy of the 1947 partition of British India plays a significant role. Along religious lines, the partition caused riots and mass migrations, leaving a lasting impact on relations. International Involvement: Global powers have strategic and economic interests in the region, influencing the conflict dynamics. The international community has been concerned with various attempts at mediation and resolution. The G20 summit, which India is hosting in 2023, is another platform where the Kashmir issue may be raised or sidelined by the two countries, depending on their strategies and objectives. Pakistan has opposed India’s decision to hold a G20 meeting in Srinagar, the capital of Indian-administered Kashmir. Conversely, India has asserted its sovereignty over the entire region and dismissed Pakistan’s objections. The G20 summit may also offer an opportunity for dialogue and cooperation between India and Pakistan on other global issues, such as climate change, economy, and development. Kashmir’s rich natural resources, including fruits, saffron, and minerals, offer economic benefits. India and Pakistan aim to benefit from these resources and tourism potential, adding another layer to the conflict. The India-Pakistan conflict is complex, involving religious, ideological, territorial, historical, geopolitical, and economic factors. Resolving this multifaceted issue requires addressing all these dimensions comprehensively. To research the India-Pakistan conflict, we can employ a multidisciplinary research methodology to comprehensively address the various dimensions involved: Historical Analysis, case studies, geopolitical analysis, and economic analysis.